Analytic theism : a philosophical investigation - Sijuwade, Joshua R. (Joshua Reginald) (New York, NY : Routledge, 2024)
"This book explores and develops a new philosophical argument for the existence of God from metaphysics. It focuses on exploring the pressing questions of God's existence, the truth of theistic belief, and its relevance in modern philosophy. In doing so, it bridges the discussions and debates in the field of contemporary metaphysics with that of analytic philosophy of religion. At its core, metaphysics is dedicated to unveiling the fundamental structure of reality, playing a critical role in any intellectual endeavour in the quest for truth. However, a noticeable gap has persisted between today's metaphysical conversations and the debates in analytic philosophy of religion, especially regarding the topic of God's existence. In this book, the author embarks on a rigorous exploration, presenting an innovative a posteriori argument for theism, rooted in the latest evidence and theories from contemporary metaphysics. The first part of the book details the explanatory framework of the analysis, which is focussed on introducing a new abductive methodology within metaphysics that provides a way for assessing the veracity of the Theism and the leading fundamental theories in contemporary metaphysics. The second part of the book then focuses on demonstrating how the central concepts and theories within contemporary metaphysics-such as quantum foundations, four-dimensionalism, formal ontology, essentialism, grounding, powerful causation, mereology, free will, personhood and the reality of suffering-are best explained by the existence of God, and thus justify theism, over that of the competing theories within contemporary metaphysics. Theism is thus the best working metaphysical theory and should take a central place in fundamental enquiries within the field of contemporary metaphysics and beyond. Analytic Theism: A Philosophical Investigation is a must-read for scholars and advanced students venturing into philosophy of religion and metaphysics. Beyond its appeal to those in analytic philosophy of religion and metaphysics, this work also resonates with those immersed in contemporary philosophy on a whole, and related fields of inquiry, serving as a pivotal read for anyone keen on the intersections of philosophy, theology, and science"--
Keywords: Theism; God -- Proof; Metaphysics; PHILOSOPHY / Metaphysics; PHILOSOPHY / Religious